The complete chloroplast genome sequence of traditional Chinese medicine Uncaria macrophylla (Rubiaceae) - Miao Zhang; Min-Min Chen; Xue-Min Zhang; Shao-Ning Chen; Zong-Suo Liang (Mitochondrial DNA. Part B. Resources, 2022)
Uncaria macrophylla (Rubiaceae) is a medicinal vine plant of the Rubiaceae family that was distributed in East Asia and Southeast Asia. The first complete chloroplast genome of Uncaria macrophylla was sequenced and assembled in this study. The genome is 155,138 bp in length and contained 129 encoded genes in total, including 79 protein-coding genes, eight ribosomal RNA genes, and 37 transfer RNA genes. The phylogenomic analysis showed that U. macrophylla was closely related to Uncaria rhynchophylla according to the current sampling extent.